KEPADATAN DAN KEANEKARAGAMAN MAKROZOOBENTHOS DI DANAU HANJALUTUNG DAN SUNGAI RUNGAN KOTA PALANGKA RAYA: Density and Diversity Macrozoobenthos in Hanjalutung Lake and Rungan River Palangka Raya City - Linda Wulandari; Satna K Simbolon; Evi Veronica; Rosana Elvince (Jurusan Perikanan Fakultas Pertanian, Kehutanan dan Perikanan, Universitas Palangka Raya (UPR), 2026)
This study aims to determine the density and diversity of macrozoobenthos and water quality conditions including temperature, depth, turbidity, pH and DO in Lake Hanjalutung and Rungan River. This research was conducted in July 2023 at Lake Hanjalutung. The results showed that at the study site found as many as 15 species of macrozoobenthos included in 3 phyla namely Uniramia, Annelida and Nematoda. The average macrozoobenthos density value ranged from 134-1,032 ind/m2. The average of diversity index values ranged from 0.714 to 1.278 indicating the diversity of macrozoobenthos species classified as low to moderate. The condition of water quality parameters at the study site showed the value of the temperature parameter was still suitable for the life of aquatic organisms. Meanwhile, the pH and DO parameter values showed relatively low values at all stations, but these values are still suitable for waters influenced by peat swamp ecosystems because they are still in their natural conditions. While the value of the turbidity parameter at station IV and the depth value at station II were higher than the other stations. Anova results on the value of diversity showed no difference between stations. While the density values showed there were differences between observation stations. Anova result on physical and chemical water quality parameters showed no difference in temperature, turbidity, pH and DO values between stations. Keywords: Macrozoobenthos, water quality parameters, Lake Hanjalutung